Three Jews of English literature: Marlowe's Barabas, Shakespeare's Shylock, and Scott's Isaac - Matherly, Ernest Wilson (My University, 1906)
Introduction: Many years before Marlowe produced his first works, that is during the reign of “Richard the First or Lionhearted,” the Jew played, perhaps, his greatest part in English history; and, though banished from England a little later than this, several historians say there were Jews in England at the time of Marlowe and of Shakespeare who played a great part in English history and from the daily lives or characters of whom both writers might have taken some thoughts upon which to found their productions. The fact is that at that time there was a Jewish Doctor, Lopez by name, who being of Spanish blood and able to speak several tongues, among them Portuguese, became interpreter for a Portuguese refugee who had fled from justice in Spain to England for protection and whom, through hatred for Spain, Elizabeth accepted and playfully termed “King Antonio.” Lopez, owing to his position as interpreter and his relation to Elizabeth, to the refugee and to the Earl of Essex became a close friend of the queen and revealed to her one of the political intrigues which the earl was about to undertake.
Citation: Matherly, Ernest Wilson. Three Jews of English literature: Marlowe's Barabas, Shakespeare's Shylock, and Scott's Isaac. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Literature; Jews; Marlowe; Shakespeare; Scott; Theses; Manuscripts (documents)